Consumption Technology and the Intrafamily Distribution of Resources: Adult Equivalence Scales Reexamined - Gronau, Reuben (Journal of Political Economy, 1988)
Adult equivalence scales are supposed to measure differences in the "needs" of households of different demographic composition. Formally, they purport to measure the change in the cost of attaining a certain welfare level when the family composition varies. This paper shows that the definition and the measurement of these scales depend crucially on the concept of welfare used. When welfare is the utility parents derive from their own consumption, one has to assume separability of parents' and children's consumption. This assumption implies that the only way of imputing the intrafamily allocation of resources is by observing the consumption patterns of adult goods. Regardless of the definition used, one cannot separate the factors reflecting home technology (i.e., "needs") from those determining the intrafamily distribution rule (i.e., "wants") out of consumption data.